2015
DOI: 10.1111/aor.12507
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Spirometry After Left Ventricular Assist Device Implantation

Abstract: Left ventricular assist devices (LVADs) are increasingly being used as life-saving therapy in patients with end-stage heart failure. The changes in spirometry following LVAD implantation and subsequent unloading of the left ventricle and pulmonary circulation are unknown. In this study, we explored long-term changes in spirometry after LVAD placement. In this retrospective study, we compared baseline preoperative pulmonary function test (PFT) results to post-LVAD spirometric measurements. Our results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Remarkably, the study data showed a profound decrease in pulmonary D LCO post-LVAD implantation consistent with findings of Mohamedali et al 18 This decline remained significant when corrected for V A (Figure 2) and was clearly evident in subsequent analyses of the 6MG and 12MG.…”
Section: Diffusing Capacity Of the Lung For Carbon Monoxidesupporting
confidence: 90%
“…Remarkably, the study data showed a profound decrease in pulmonary D LCO post-LVAD implantation consistent with findings of Mohamedali et al 18 This decline remained significant when corrected for V A (Figure 2) and was clearly evident in subsequent analyses of the 6MG and 12MG.…”
Section: Diffusing Capacity Of the Lung For Carbon Monoxidesupporting
confidence: 90%
“…A reduced ventilation efficiency (Ve/ VCO2>35) was measured in 52 patients (63%). It is unclear whether respiratory function improves after CF-LVAD implantation [24,25], but it is commonly agreed that CF-LVAD patients show an impaired respiratory muscle function and/or ventilation-perfusion mismatch [4].…”
Section: Limiting Factors Of Submaximal Exercisementioning
confidence: 99%
“…Nevertheless, general health conditions of both experimental animals were mostly stable, with no dramatic disturbances. Mohamedali et al reported in their recent paper significant reduction of pulmonary functions resulting from long-term implantation of LVAD (22). In both HF-TAH experiments the dominant histological finding in samples from kid-neys was a proteinaceous material in lumen of glomeruli and tubules.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical and experimental studies also indicate that long-term implantation of circulation support devices may be related to more or less extensive changes of the respiratory system. Mohamedali et al reported in their recent paper significant reduction of pulmonary functions resulting from long-term implantation of LVAD (22). Baba et al observed in their experiments with UPTAH signs of intra-alveolar edema, hemorrhagic foci, pulmonary vessels thrombosis, atelectasis, and various degrees of inflammatory infiltration (18).…”
Section: Discussionmentioning
confidence: 99%